2019
DOI: 10.4103/jfmpc.jfmpc_424_19
|View full text |Cite
|
Sign up to set email alerts
|

Culture positivity of smear negative pulmonary and extrapulmonary tuberculosis- A study from North Kerala, India

Abstract: Introduction:The identification of smear negative pulmonary and extrapulmonary tuberculosis continues to remain a diagnostic challenge. This study was conducted in a tertiary care setup in north Kerala to isolate and identify mycobacteria by culture from radiologically and clinically suspected cases of smear negative pulmonary and extrapulmonary tuberculosis.Methods:A total of 200 samples (100 pulmonary and 100 extrapulmonary) were processed and cultured by automated (MB/BacT) and conventional methods. Heat st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…With references cited from various studies, since a positive culture for TB in extrapulmonary TB is very low, which can cause significant delay in initiation of treatment, our patient was started ATT with cytology of granulomatous inflammation which helped in decreasing the morbidity and mortality. 17,18 Review of various literatures revealed, a case report on 21 years old male with immunocompromised state and IgA deficiency with recurrent subdiaphragmatic collection as an unusual extrapulmonary manifestation of tuberculosis was reported for the first time in 2006. 1 Patient was hospitalised frequently for subphrenic abscess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With references cited from various studies, since a positive culture for TB in extrapulmonary TB is very low, which can cause significant delay in initiation of treatment, our patient was started ATT with cytology of granulomatous inflammation which helped in decreasing the morbidity and mortality. 17,18 Review of various literatures revealed, a case report on 21 years old male with immunocompromised state and IgA deficiency with recurrent subdiaphragmatic collection as an unusual extrapulmonary manifestation of tuberculosis was reported for the first time in 2006. 1 Patient was hospitalised frequently for subphrenic abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Cytology from pigtail site showed an inflammatory smear p/o granulomatous inflammation. 18 A positive culture for TB from intraperitoneal fluid is low and takes 6 to 8 weeks, which can cause significant delay in initiation of treatment, with expert opinion, patient was started on anti-tuberculous therapy. In 2 weeks, patient's abdomen pain, breathlessness, fever and pus discharge from sinus settled.…”
Section: Case Reportmentioning
confidence: 99%
“…Direct and concentrated smears were prepared from clinical specimens by using modified Petroff's method [7]. Specimens were treated with 4 % NaOH for decontamination and digestion of clinical specimens.…”
Section: Smear Preparation and Culturementioning
confidence: 99%
“…It was reported that smear negative TB patients spread disease among 20% of total TB cases in the Republic of Congo [6]. Culture for MTB still stands as the most standardized test for definitive diagnosis but it considerably delays the results [7]. In high TB prevalent settings, suspected cases with at least two negative reports of sputum samples are given unspecified chemotherapeutic agents for 15 days and then advised for another sputum sample followed by a chest x-ray.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of TB is not possible without microbiological evidence while many patients remain with smear negative pulmonary TB (SNPT) for weeks and months further smear negative patients have been reported to spread TB among 20% cases [7]. Culture for MTB is considered as gold standard for sure diagnosis of TB which significantly delays the results due to number of reasons [8]. Similarly in cases with SNPT a complicated criterion is carried out for imperial treatment unless conclusive diagnosis is made which not only delays the standard treatment but also threatens in spread of disease to many healthy contacts [7].…”
Section: Introductionmentioning
confidence: 99%